IMPAIRED REGULATORY MECHANISMS OF THE mTOR SIGNALING PATHWAY IN OSTEOARTHROSIS - Elena Vasilyevna Chetina; E A Bratygina; E M Zaitseva; E P Sharapova; A L Alekseyeva; N V Demin; S A Makarov (Научно-практическая ревматология)
Objective: to study the pattern of impaired regulatory mechanisms of the mammalian target of rapamycin (TOR) signaling pathway, by monitoring gene expression in the blood of patients with osteoarthrosis (OA) at different stages of the disease. Subjects and methods. The study covered 33 outpatients with OA, 14 patients with this condition prior to knee joint endoprosthesis, and 27 healthy individuals (controls) (mean age 58.0+7.4, 56.5+8.9, and 55.0+8.3 years, respectively). Total RNA was isolated from their blood and used to determine the level of gene expression by a real-time polymerase chain reaction for AMP-activated protein kinase (AMPK), hypoxia-inducible factor-1α (HIF1α), the rate-limiting proteins of the hexosamine signaling pathway — glutamine-fructose-6-phosphate amidotransferase and acetylglucosaminyltransferase, as well as the glucose transporter GLUT1 and steps 6 and 7 glycolytic pathway components — glucose-6-phosphate dehydrogenase and phosphoglycerate kinase-1, respectively; the lipogenesis-related genes — fatty acid synthase (FAS) and the activity of the pentose phosphate pathway — glucose-6-phosphate dehydrogenase in the blood of patients with OA at different stages of the disease. Results. Analysis of gene expressions showed that in the OA patients with a low expression of the mTOR gene (a LOW subgroup), the expression of AGT and GLUT1 genes proved to be significantly lower and that of the AMPK gene was higher than in the healthy individuals. In the OA patients with a high expression of the mTOR gene (a HIGH subgroup), the expression of all the genes under study was much higher, except for the FAS gene; moreover, the greatest expression excess as compared to the controls was observed for the AMPK and HIFlα genes. In the patients with endstage disease (an ES subgroup), the expression of all the study genes, including the FAS gene, turned out to be higher than in the healthy individuals. Conclusion. The development of OA is accompanied by a considerable decrease in the efficiency of energy metabolism. At the same time, in the patients with a low mTOR gene expression, energy deficiency may be due to decreased cellular metabolite transport. It may be caused by the deficiency of the end electron acceptor oxygen in the patients with a high mTOR gene expression and the pathological redistribution of energy substrate in favor of lipogenesis cannot be ruled out in those with end-stage disease.